Nematic compounds and mixtures with high negative dielectric anisotropy. Issue 10 (9th August 2017) - Dąbrowski, R.; Dziaduszek, J.; Garbat, K.; Urban, S.; Filipowicz, M.; Herman, J.; Czerwiński, M.; Harmata, P.
ABSTRACT: Syntheses, mesogenic and dielectric properties of three-ring alkylcyclohexyl, alkoxy and alkylphenyl benzoates substituted with four fluorine atoms or with two fluorine atoms and simultaneously a cyano group or two cyano groups are described. Their properties are compared with analogous three-ring phenyl tolanes. Conformation analysis and the calculation of dipole moments with the quantum chemistry method are performed to explain the experimental results. Several four fluorine-substituted two-ring tolanes and biphenyls are also prepared, which are used as a solvent decreasing viscosity, melting point and clearing point of the formulated mixtures. Examples of mixtures prepared from the esters and tolanes with high dielectric anisotropy are given. Curiosity is observed that 4ʹ-(4-ethoxyphenyl)-4-pentyloxy-2, 2ʹ, 3, 3ʹ-tetrafluorotolane is not the mesogenic compound, while analogous ester 4ʹ-ethoxy-2, 3-difluorobiphenyl-4-yl 2, 3-difluoro-4-pentyloxybenzoate exhibits a broad temperature range of the nematic phase. Graphical Abstract: